Engineering economy - Blank, Leland T.; Tarquin, Anthony J. (New York : Mc Graw Hill, 2008)
Features solved examples, problems and case studies that target many of engineering challenges in areas such as energy, ethics, the environment, and the world's changing economics. This title presents a design using color, highlighting icons to focus on important concepts, terms, equations and decision guidelines.
Includes bibliographical references and index.
Keywords: Engineering economy